Connecting architecture to the electronic age: the effects of mass media as seen through architecture - Nelson, David (School of Architecture, Planning and Geomatics, 2024)
Architecture and society have been affected by a new paradigm: a shift from the mechanical age to the electronic. At the beginning of the twentieth century, modernist architects created new aesthetics, new forms, new representational techniques and new symbols of the industrial society. Equivalents could be found in the electronic age; one could investigate new signs and systems that reflect the information society. The information age or electronic age is governed by the rise of technology that has created a media culture of constant change, instantaneous imagery and mass communication. This thesis design strives to capture the affects that the electronic age has on society, translating these into a building that can communicate with the contemporary media culture. The signs and symbols that define this age are dynamic and are in a constant state of motion; they include: mass information, connectivity, media and computer interaction. These influences are largely immaterial and based on information flows, thus the design needs to translate these immaterial influences into the scale of human interaction and cognition. One needs to understand the dynamic relationship between media and architecture, between the virtual world and the physical space. The virtual body represents the electronic flows and the limitless affects of media; the architecture represents the essence of physical space that still craves the sensual and technical experiences of the physical world. The virtual realm has not replaced the physical realm; it can be argued that as media has become ever more vital, the development of our physical space has become even more important. It is the dynamic relationship of the two that has the potential to create physical spaces that can transport one into an overlapping experience of real and virtual. The impact of communication media has affected the practice of architecture and the way in which we experience our environments. This paper will strive to understand the forces of the electronic age and the potential ways these forces can be manifested into the built environment. The instantaneous imagery, mass communication and constant motion of the electronic age urges one to redefine the way architecture communicates with society. Through materiality, space and form, how can a building constantly engage with a society that is in regular connection to the motion of mass media? Can the understandings of the virtual be utilised to enhance the experience of a physical space - a space that is in constant motion and continually being reinvented by virtual influences? The electronic age has also affected how we live, work and play, thus urging one to reanalyse the way that we design living space, office space, communication space, relaxing space and inspirational space. Throughout this paper I will continuously relate my theoretical findings to the way in which I believe these spaces can be designed.